Investigation of thermal conductivity and viscosity of Al2O3/water–ethylene glycol mixture nanocoolant for cooling channel of hot-press forming die application. (November 2016) - Lim, S.K.; Azmi, W.H.; Yusoff, A.R.
Abstract: Hot-press forming process is widely used to produce lightweight chassis in automotive industries. The hot-press forming process currently uses water as coolant to quench boron steels in a closed die with a cooling channel. However, to enhance performance of hot-press forming die, the fluid with better thermal properties will be used instead of normal water. This study dispersed Al2 O3 nanoparticles with an average diameter of 13 nm in three volume percentages base ratios of water (W) to ethylene glycol (EG) (i.e. 60:40, 50:50, and 40:60) by two-step preparation. The two main parameters in cooling rate performance are thermal conductivity and viscosity. The nanocoolant of Al2 O3 /water–ethylene glycol mixture is prepared for the volume concentration range of 0.2 to 1.0%. The thermal conductivity and viscosity are then measured at temperature range of 15 to 55 °C. The highest enhancement of thermal conductivity was observed to be 10% higher than base fluid for 1.0% volume concentration at 55 °C in 60:40 (W/EG). However, the highest enhancement of viscosity was measured to be 39% for 1.0% volume concentration in 40:60 (W/EG) at 25 °C. The convective heat transfer coefficient of 1.0% concentration in 60:40 (W:EG) at 25 °C is enhanced by 25.4% better than that of 50:50 and 40:60 (W:EG) base fluid. Therefore, this study recommends the use of Al2 O3 in 60:40 (W:EG) mixture with volume concentration of less than 1.0% for application in cooling channel of hot-press forming die. Nanocoolant as cooling agent with higher heat transfer coefficient compared to the base fluid can reduce the cycle time and increase the productivity of hot-press forming process.